Ectopic USP15 expression inhibits HIV-1 transcription involving changes in YY1 deubiquitination and stability - Rezaei, Sahar; Timani, Khalid A.; Liu, Ying; He, Johnny J. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionProtein homeostasis is maintained by the opposing action of ubiquitin ligase and deubiquitinase, two important components of the ubiquitin-proteasome pathway, and contributes to both normal physiological and pathophysiological processes. The current study aims to delineate the roles of ubiquitin-specific protease 15 (USP15), a member of the largest deubiquitinase family, in HIV-1 gene expression and replication.MethodsWe took advantage of highly selective and specific ubiquitin variants (UbV), which were recently designed and developed for USP15, and ascertained the inhibitory effects of USP15 on HIV-1 gene expression and production by transfection and Western blotting. We also used real-time RT-PCR, transcription factor profiling, subcellular fractionation, immunoprecipitation followed by Western blotting to determine the transcription factors involved and the underlying molecular mechanisms.ResultsWe first confirmed the specificity of USP15-mediated HIV-1 gene expression and virus production. We then showed that the inhibition of HIV-1 production by USP15 occurred at the transcription level, associated with an increased protein level of YY1, a known HIV-1 transcription repressor. Moreover, we demonstrated that USP15 regulated YY1 deubiquitination and stability. Lastly, we demonstrated that YY1 siRNA knockdown significantly diminished the inhibition of USP15 on HIV-1 gene expression and virus production.ConclusionThese findings together demonstrate that stabilization of YY1 protein by USP15 deubiquitinating activity contributes to USP15-mediated inhibition of HIV-1 transcription and may help the development of USP15-specific UbV inhibitors as an anti-HIV strategy.